Opinion survey on the profession of a physiotherapist in Poland - Kacper Pajor; Paweł Szumilas (Kazimierz Wielki University, 2021)
Introduction Despite numerous activities of the National Chamber of Physiotherapists, there are reasons that question the organization of physiotherapy in Poland. Public services are particularly criticized, which is alarming, because physiotherapy that functions well within the public health service is essential for maintaining the optimal efficiency of the entire system. Purpose Determining the current opinion on the profession of a physiotherapist and the process of physiotherapy in Poland, taking into account the differences between reimbursed services and those provided in non-public entities. Material and method The method of diagnostic survey distributed with the use of social networks was used. The study group included 164 people (53F, 111M). Results The quality of private services was statistically significantly (p <.0001) assessed better on a five-point scale (4.74 [SD = 0.44]) than reimbursed services (3.1 [SD = 1.20]). Comparing the opinion on commercial services with those provided under public health care, significant (p <.0001) differences were also noted in other assessed aspects in favor of private physiotherapy, which was assessed as good. Public health services were rated averagely. Conclusions Public health care physiotherapy is rated worse than commercial services. People who have undergone physiotherapy financed by the National Health Fund would be less willing to start physiotherapy again if necessary than people with experience from private physiotherapy offices. Activities optimizing the work system of physiotherapists can improve the opinion about physiotherapy in public health care in Poland, giving measurable health and economic benefits in the long term.